CryoTEM Study of Effects of Phosphorylation on The Hierarchical Assembly of Porcine Amelogenin and Its Regulation of Mineralization in vitro - Fang, Ping-An (2013)
Amelogenin, the major extracellular enamel matrix protein, plays a critical role in regulating the growth and organization of enamel. Assembly and mineralization of full-length native (P173) and recombinant (rP172) porcine amelogenins were studied by cryogenic Transmission Electron Microscopy (cryoTEM). The cryoTEM revealed that both native and recombinant porcine amelogenins undergo step-wise self-assembly. Although the overall structural organization of P173 and rP172 oligomers was similar and resembled oligomers of murine recombinant amelogenin rM179, there were subtle differences suggesting that a single phosphorylated serine present in P173 might affect amelogenin self-assembly. Our mineralization studies demonstrated that both P173 and rP172 oligomers stabilize initial mineral clusters. Importantly, however, rP172 regulated the organization of initial mineral clusters into linear chains and guided the formation of parallel arrays of elongated mineral particles, which are the hallmark of enamel structural organization. These results are similar to those obtained previously using full-length recombinant murine amelogenin (Fang et al., 2011a). In contrast to that seen with rP172, phosphorylated P173 strongly inhibits mineralization for extended periods of time. We propose that these differences might be due to the differences in the structural organization and charge distribution between P173 and rP172. Overall our studies indicate that self-assembly of amelogenin and the mechanisms of its control over mineralization might be universal across different mammalian species. Our data also provide new insight into the effect of phosphorylation on amelogenin self-assembly and its regulation of mineralization.